Bowel Movement: Integrating Host Mobility and Microbial Transmission Across Host Taxa - Weinhold, Arne (Frontiers in Microbiology, 2022)
The gut-microbiota of animals displays a high degree of plasticity with respect to environmental or dietary adaptations and is shaped by factors like social interactions, diet diversity or the local environment. But the contribution of these drivers varies across host taxa and our ability to explain microbiome variability within wild populations remains limited. Terrestrial animals have divergent mobility ranges and can either crawl, walk or fly, from a couple of centimeters towards thousands of kilometers. Animal movement has been little regarded in host-microbiota frameworks, though it can directly influence major drivers of the host microbiota: (1) Aggregation movement can enhance social transmissions, (2) foraging movement can extend range of diet diversity, and (3) dispersal movement determines the local environment of a host. Here, I would like to outline how movement behaviors of different host taxa matter for microbial acquisition across mammals, birds as well as insects. Host movement can have contrasting effects and either reduce or enlarge spatial scale. Increased dispersal movement could dissolve local effects of sampling location, while aggregation could enhance inter-host transmissions and uniformity among social groups. Host movement can also extend the boundaries of microbial dispersal limitations and connect habitat patches across plant-pollinator networks, while the microbiota of wild populations could converge towards a uniform pattern when mobility is interrupted in captivity or laboratory settings. Hence, the implementation of a host movement would be a valuable addition to the metacommunity concept, to comprehend microbial dispersal within and across trophic levels.